PENGARUH JARINGAN BISNIS, TEKNOLOGI PRODUKSI, DAN PENJAMINAN MUTU TERHADAP KINERJA PEMASARAN (Studi pada IKM gitar Di Kecamatan Baki, Kabupaten Sukoharjo) - Pranoto Utomo; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2017)
economy of Indonesia. Undeniable small and medium enterprises (SMEs) is one of the drivers of economic growth in Indonesia. Amid the global crisis which hit many countries in the world, Indonesia proved to be able to continue to survive the economic turmoil. Various SMES growing in Indonesia, one of them is creating guitar in the village of Mancasan, Kec. Baki, Kab. Sukoharjo. Mancasan village is famous as a Center for the manufacture of the guitar because the majority of the residents of the village of Mancasan is the crafters of guitar. But in its development of competition with competitors that are moving on the same type of business make SME guitar in Kec. Baki should implement a range of strategies that can improve the performance of the market.The purpose of this research is to know the influence of business networks, production technology, quality assurance and marketing performance SMEs of guitar in Kec. Baki, Kab. Sukoharjo. This research type is explanatory research. The population in this study i.e. crafters of guitar and SME number of samples taken is 63 respondents. Sampling techniques in the study using a non probability sampling with purposive sampling technique. Methods of analysis used is cross-tabulations, correlation, linear regression, the determination of the simple, double, t-test and F-test with SPSS program version.Based on the results of the research note that the network business, production technology, quality assurance and a positive and significant effect on performance marketing, whether partial or simultaneous. Free variables that have the greatest influence on performance marketing is a business network variables. As for the advice that can be given to maintaining and enhancing the harmony with a partner, providing a period of training for employees in the future so that raw doesn't do a lot of faults, select human resources, give promo and make sales online in order to increase the pace of sales that will have an impact on the acquisition of profit is received so that the company can keep his survival.